2017
DOI: 10.1111/cbdd.13070
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of the interaction between taxifolin (dihydroquercetin) and pyrimethamine against Toxoplasma gondii

Abstract: Toxoplasmosis is one of the most neglected zoonotic foodborne parasitic diseases that cause public health and socioeconomic concern worldwide. The current drugs used for the treatment of toxoplasmosis have been identified to have clinical limitations. Hence, new drugs are urgently needed to eradicate T.gondii infections globally. Here, an in vitro anti-Toxoplasma gondii activity of taxifolin (dihydroquercetin) and dihydrofolate inhibitor (pyrimethamine) alone and in combination with a fixed concentration of py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 57 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…Previous reports showed possible beneficial effects of taxifolin using animal models, including improvement of microcirculation [5], hepatoprotective effects [6], anti-viral activity [7], and prevention of diabetic nephropathy [8] as well as cardiomyopathy [9]. Further, in vitro studies demonstrated that taxifolin exhibits anti-bacterial [10], anti-fungal [11], and anti-parasitic [12] effects, and taxifolin inhibits acetylcholinesterase and carbonic anhydrase isoenzymes [13]. Taxifolin also inhibits oligomer formation of amyloid β proteins in mice, and is thought to be effective to prevent Alzheimer related diseases [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed possible beneficial effects of taxifolin using animal models, including improvement of microcirculation [5], hepatoprotective effects [6], anti-viral activity [7], and prevention of diabetic nephropathy [8] as well as cardiomyopathy [9]. Further, in vitro studies demonstrated that taxifolin exhibits anti-bacterial [10], anti-fungal [11], and anti-parasitic [12] effects, and taxifolin inhibits acetylcholinesterase and carbonic anhydrase isoenzymes [13]. Taxifolin also inhibits oligomer formation of amyloid β proteins in mice, and is thought to be effective to prevent Alzheimer related diseases [14].…”
Section: Introductionmentioning
confidence: 99%
“…Taxifolin is known to be an antioxidant agent [3], and is known for the many beneficial effects of taxifolin, such as improvement of microcirculation [4], hepatoprotective effects [5], anti-viral activity [6], and prevention of diabetic nephropathy [7] as well as diabetic cardiomyopathy [8]. In vitro studies have demonstrated that taxifolin exhibits anti-bacterial [9], anti-fungal [10], and anti-parasitic [11] effects, and also inhibitory activities against acetylcholinesterase and carbonic anhydrase isoenzymes [12]. Further, oligomer formation of amyloid β proteins is significantly inhibited by taxifolin in mice, suggesting that taxifolin is effective to prevent Alzheimer's disease [13].…”
Section: Introductionmentioning
confidence: 99%
“…The safety of DHQ also has been investigated since it is a key component of dietary supplements 2 . Additionally, DHQ has a wide range of pharmacological activities, including anti-inflammatory 3 , anti-microbial 4 anti-cancer 5 , anti-Alzheimer 6 , anti-toxoplasmosis effects 7 , health-promoting effects on hepatoprotective and cardiovascular systems 8 , 9 . Due to its excellent pharmacological activity, DHQ is routinely used in pharmaceuticals, health products, foods and agriculture.…”
Section: Introductionmentioning
confidence: 99%